The ‘Ciompi Revolution’ Constructed: Modern Historians and the Nineteenth-Century Paradigm of Revolution - Lantschner, Patrick (Annali di Storia di Firenze, 2011)
To this day the Ciompi revolt of 1378 has provoked fierce debate between historians of different political persuasions. This article proposes, however, that liberal, conservative and Marxist historians from the last two centuries and different countries have fundamentally argued within the same paradigm of research which has conditioned their conceptualisation, interpretation and narration of the Ciompi revolt. Ciompi historians have recurred to the same concepts of ‘state’, ‘class’ and ‘revolution’, and their related normative connotations and narrati- ve assumptions. In their analyses of the Ciompi revolt, they thus came to replicate a modern understanding of politics and its correspondent ideological divisions.